What is the cognitive footprint of insular glioma? - Nichols, Noah M.; Ezzat, Bahie; Waters, Allison C.; Panov, Fedor; Yong, Raymund L.; Germano, Isabelle M. (Frontiers in Human Neuroscience, 2024)
Cognitive impairment has a profound deleterious impact on long-term outcomes of glioma surgery. The human insula, a deep cortical structure covered by the operculum, plays a role in a wide range of cognitive functions including interceptive thoughts and salience processing. Both low-grade (LGG) and high-grade gliomas (HGG) involve the insula, representing up to 25% of LGG and 10% of HGG. Surgical series from the past 30 years support the role of primary cytoreductive surgery for insular glioma patients; however, reported cognitive outcomes are often limited to speech and language function. The breath of recent neuroscience literature demonstrates that the insula plays a broader role in cognition including interoceptive thoughts and salience processing. This article summarizes the vast functional role of the healthy human insula highlighting how this knowledge can be leveraged to improve the care of patients with insular gliomas. The human insula plays a role in a wide range of cognitive functions including interceptive thoughts and salience processing. Insular gliomas represent up to 25% of low-grade gliomas and 10% of high-grade gliomas. Many large case series over the past 30 years have demonstrated acceptable rates of morbidity and mortality after insular glioma surgery. Language outcomes following insular tumor surgery have been widely reported; however, other aspects of higher cognition are often not discussed. The breadth of recent neuroscience studies examining the functional role of the human insula have not been fully translated to patients with intrinsic tumors in this region.